Quantifying the Probing and Selection of Microenvironmental Pores by Motile Immune Cells. Issue 4 (5th April 2022) - Kroll, Janina; Ruiz‐Fernandez, Mauricio J. A.; Braun, Malte B.; Merrin, Jack; Renkawitz, Jörg
Abstract: Immune cells are constantly on the move through multicellular organisms to explore and respond to pathogens and other harmful insults. While moving, immune cells efficiently traverse microenvironments composed of tissue cells and extracellular fibers, which together form complex environments of various porosity, stiffness, topography, and chemical composition. In this protocol we describe experimental procedures to investigate immune cell migration through microenvironments of heterogeneous porosity. In particular, we describe micro‐channels, micro‐pillars, and collagen networks as cell migration paths with alternative pore size choices. Employing micro‐channels or micro‐pillars that divide at junctions into alternative paths with initially differentially sized pores allows us to precisely (1) measure the cellular translocation time through these porous path junctions, (2) quantify the cellular preference for individual pore sizes, and (3) image cellular components like the nucleus and the cytoskeleton. This reductionistic experimental setup thus can elucidate how immune cells perform decisions in complex microenvironments of various porosity like the interstitium. The setup further allows investigation of the underlying forces of cellular squeezing and the consequences of cellular deformation on the integrity of the cell and its organelles. As a complementary approach that does not require any micro‐engineering expertise, we describe the usage of three‐dimensional collagen networks with different pore sizes. Whereas we here focus on dendritic cells as a model for motile immune cells, the described protocols are versatile as they are also applicable for other immune cell types like neutrophils and non‐immune cell types such as mesenchymal and cancer cells. In summary, we here describe protocols to identify the mechanisms and principles of cellular probing, decision making, and squeezing during cellular movement through microenvironments of heterogeneous porosity. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Immune cell migration in micro‐channels and micro‐pillars with defined pore sizes Support Protocol 1 : Epoxy replica of generated and/or published micro‐structures Support Protocol 2 : Dendritic cell differentiation Basic Protocol 2 : Immune cell migration in 3D collagen networks of variable pore sizes